The effect of FDI on Economic Growth of the Kazakhstan and Investment opportunities in different regions of Kazakhstan - Amangaliyeva, Anara (2021)
This work examines the impact of FDI flows and its changes on Economic Growth of Kazakhstan for the period between 1993 and 2019. Moreover, the insight on top invested regions and their investment potentials will be outlined as well as FDI numbers and macroeconomic indicators such as return on investment, exchange rate, net capital inflow that will provide data on those selected regions. Investment attractiveness of transitionary economies will be analyzed and compared to the Kazakhstan’s case, as well as the evidence on FDI attractiveness of each country and their locations.